Sammutusjätevesien hallinta ja ympäristövaikutukset Suomessa - Rintala, Ida (2018)
he water used to extinguish fire may end up to the surface water and through soil to the groundwater. This water may contain hazardous chemicals and cause transboundary effects. In this MSc thesis, the valid legislation and instructions on firewater were collected. In addition, it was determined which parameters should be analyzed in firewater. There was also an online survey sent to the competent authorities and operators to find out how informed they are of the legislation and instructions and to find out their perspectives to evaluate the environmental impacts and firewater management. The sufficient legislation and instructions exist, but authorities are inadequately informed of those. Most competent authorities were in favor of including the management of firewater in the environmental permit at least on a case-by-case basis. To promote safety guidelines and good practices, simple and clear instructions to firewater management should be developed. The guide should be applicable to different industries and taken into account the requirements of different authorities. The competent authorities should co-operate for providing the implementation of legislation and instructions to prevent accidental pollution. In the future, there should be systematic studies as well as database to establish a sector-specific guideline to determine the quality of firewater.